Proposed module for developing critical thinking skills in teaching the concept of resources - Laking, Artemio Tayab 1943- (1977)
The purpose of the study was to propose a supplementary course module on the concept of Resources to develop some basic thinking skills among first year students. The methodology employed by the study includes identification of the problem on how to develop thinking skills, specification of the objectives of module, design of supplementary module for developing thinking skills among first year students using the concept Resources as a subject area, examination of relevant professional books, magazines and other unpublished materials, and writing of the module. The study concluded that to develop cognitive thinking skills through self-instructional modules, both the teacher and the learner must be aware of their respective obligations or responsibilities. An awareness of this is the basic prerequisite for success in attaining the objectives. This should be followed by that personal direction constituting right habits and attitudes of learning or teaching and finally, the willingness and ability of the student to undertake the activities required in the module.